Pengaruh Experiential Marketing, Brand Ambassador, Electronic Word of Mouth (E-WOM) Terhadap Keputusan Pembelian Kosmetik Lokal Merek ‘Somethinc’ - Roberto (Journal of Indonesian Economic Research, 2025)
This study aims to examine the effect of experiential marketing, brand ambassador and electronic word of mouth on purchasing decisions on local brands Somethinc. The type of research is classified as quantitative research. The sample of this study was 101 respondents who had purchase Somethinc. Data collection used with survey and questionnaires as the instrument. The data analysis techniques used are descriptive statistics, classical assumption tests, and multiple linear regression. The results proves that experiential marketing has significant effect on purchase decision, meanwhile brand ambassador and electronic word of mouth does not have significant effect on purchase decision towards local brand cosmetics Somethinc. These findings have theoretical implications for further research, exploring other variables predicted to influence purchase decisions, particularly for local cosmetic products, or expanding the research model by including mediating or moderating variables. Companies should maintain marketing strategies that actively engage consumers' five senses to enhance consumer experience. Companies should evaluate brand ambassadors who better align with the product image and market segment. Companies need to improve aspects of digital marketing to build interactive communication so consumers can trust online reviews in the digital media used by the company.